Is the LITE version of the usability metric for user experience (UMUX-LITE) a reliable tool to support rapid assessment of new healthcare technology?. (April 2020) - Borsci, Simone; Buckle, Peter; Walne, Simon
Abstract: Objective: To ascertain the reliability of a standardised, short-scale measure of satisfaction in the use of new healthcare technology i.e., the LITE version of the usability metric for user experience (UMUX-LITE). Whilst previous studies have demonstrated the reliability of UMUX-LITE, and its relationship with measures of likelihood to recommend a product, such as the Net Promoter Score (NPS) in other sectors no such testing has been undertaken with healthcare technology. Materials and methods: Six point-of-care products at different stages of development were assessed by 120 healthcare professionals. UMUX-LITE was used to gather their satisfaction in use, and NPS to declare their intention to promote the product. Inferential statistics were used to: i) ascertain the reliability of UMUX-LITE, and ii) assess the relationship between UMUX-LITE and NPS at different stages of products development. Results: UMUX-LITE showed an acceptable reliability (α = 0.7) and a strong positive correlation with NPS (r = 0.455, p < .001). This is similar to findings in other fields of application. The level of product development did not affect the UMUX-LITE scores, while the stage of development was a significant predictor (R 2 = 0.49) of the intention to promote. Discussion and conclusion: Practitioners may apply UMUX-LITE alone, or in combination with the NPS, to complement interview and 'homemade' scales to investigate the quality of new products at different stages of development. This shortened scale is appropriate for use in the context of healthcare in which busy professionals have a minimal amount of time to support innovation. Highlights: The UMUX-LITE is a reliable tool to assess healthcare technology. The UMUX-LITE provides a rapid and reliable check on the progress of a new design. UMUX-LITE may be used at different stages of product development.